Thrombosis at Unusual Sites: Focus on Myeloproliferative Neoplasms and Paroxysmal Nocturnal Hemoglobinuria - Koschmieder, Steffen; Panse, Jens (Hämostaseologie, 2025)
Patients with thrombosis at an unusual site will need to be explored for rare causes of thrombosis. Two of these rare causes include myeloproliferative neoplasms (MPNs) and paroxysmal nocturnal hemoglobinuria (PNH). It is important not to overlook these causes, since they require specific management, in addition to antithrombotic treatment (anticoagulants, antiplatelet agents). Unusual sites of venous thrombosis include upper extremity veins, splanchnic veins, cerebral veins, and retinal veins, and unusual sites of arterial thrombosis include renal, adrenal, splenic and mesenteric arteries, and intracardiac and aortal locations. Suspicion for MPN and PNH should be raised if there are concomitant abnormalities, such as elevated or decreased blood cell counts or splenomegaly. Diagnosis of MPN and PNH should include JAK2V617F mutational screening as well as flow cytometric assessment of GPI-anchored proteins in the peripheral blood, respectively. Specific treatments for MPN may include phlebotomy or cytoreductive drugs such as hydroxyurea, anagrelide, pegylated interferon-alpha, or Janus kinase inhibitors. Drugs used for PNH treatment include terminal complement inhibitors, such as eculizumab and ravulizumab, as well as proximally acting inhibitors such as pegcetacoplan or iptacopan. Patients with MPN and PNH are at high risk for thrombosis during their entire lifetime and should thus be followed by specialists experienced in the care of these diseases.
Keywords: thrombosis; unusual sites; myeloproliferative neoplasms (MPNs); paroxysmal nocturnal hemoglobinuria (PNH); complement